Analisis Faktor-Faktor Yang Mempengaruhi Waktu Tunggu Kapal (Waiting Time) Kapal Di Pelabuhan Tanjung Wangi - Anggara Dwi Tasima Putra; Siti Sahara (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The ship's berthing time may not be in accordance with the predetermined plan due to a lack of personnel for ship berthing activities. Considering this situation, ports have certain time limits, thus causing problems with ship waiting times at the port. The aim of this research is to identify factors that influence ship waiting times at Tanjung Wangi Port. The research was conducted at Tanjung Wangi Harbor for six months from August to December 2022. The source of data obtained is qualitative descriptive data, namely data obtained in the form of information resulting from discussions, both oral and written. The survey results revealed that the waiting time for ships at Tanjung Wangi Port was caused by a lack of communication and information at the time of departure, as well as bad weather due to the influence of the season in the area.